Ultrafast harmonic rf kicker design and beam dynamics analysis for an energy recovery linac based electron circulator cooler ring - Huang, Yulu; Wang, Haipeng; Rimmer, Robert A.; Wang, Shaoheng; Guo, Jiquan (Physical review. Accelerators and beams, 2016)
An ultrafast kicker system is being developed for the energy recovery linac (ERL) based electron circulator cooler ring (CCR) in the proposed Jefferson Lab Electron Ion Collider (JLEIC, previously named MEIC). In the CCR, the injected electron bunches can be recirculated while performing ion cooling for 10–30 turns before the extraction, thus reducing the recirculation beam current in the ERL to 1/10−1/30 (150mA−50mA ) of the cooling beam current (up to 1.5 A). Assuming a bunch repetition rate of 476.3 MHz and a recirculating factor of 10 in the CCR, the kicker is required to operate at a pulse repetition rate of 47.63 MHz with pulse width of around 2 ns, so that only every 10th bunch in the CCR will experience a transverse kick while the rest of the bunches will not be disturbed. Such a kicker pulse can be synthesized by ten harmonic modes of the 47.63 MHz kicker pulse repetition frequency, using up to four quarter wavelength resonator (QWR) based deflecting cavities. In this paper, several methods to synthesize such a kicker waveform will be discussed and a comparison of their beam dynamics performance is made using ELEGANT. Four QWR cavities are envisaged with high transverse shunt impedance requiring less than 100 W of total rf power for a Flat-Top kick pulse. Multipole fields due to the asymmetry of this type of cavity are analyzed. The transverse emittance growth due to the sextupole component is simulated in ELEGANT. Off-axis injection and extraction issues and beam optics using a multicavity kick-drift scheme will also be discussed.